2008
DOI: 10.1152/ajpregu.00146.2008
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo and in vitro assessment of TOR signaling cascade in rainbow trout (Oncorhynchus mykiss)

Abstract: In mammals, feeding promotes protein accretion in skeletal muscle through a stimulation of the insulin- and amino acid- sensitive mammalian target of rapamycin (mTOR) signaling pathway, leading to the induction of mRNA translation. The purpose of the present study was to characterize both in vivo and in vitro the activation of several major kinases involved in the mTOR pathway in the muscle of the carnivorous rainbow trout. Our results showed that meal feeding enhanced the phosphorylation of the target of rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
132
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 59 publications
(50 reference statements)
16
132
1
Order By: Relevance
“…In humans, Phe deficiency reduced serum insulin concentrations [63]. It was reported that low insulin concentrations decreased TOR expression in the muscle cells of rainbow trout (Oncorhynchus mykiss) [64]. These observations suggested that Phe may modulate the expression of TOR partly through affecting insulin production, which awaits further investigation.…”
Section: Phe Regulated Nf-kb P65 I-kba and Tor Gene Expressions In Tmentioning
confidence: 96%
“…In humans, Phe deficiency reduced serum insulin concentrations [63]. It was reported that low insulin concentrations decreased TOR expression in the muscle cells of rainbow trout (Oncorhynchus mykiss) [64]. These observations suggested that Phe may modulate the expression of TOR partly through affecting insulin production, which awaits further investigation.…”
Section: Phe Regulated Nf-kb P65 I-kba and Tor Gene Expressions In Tmentioning
confidence: 96%
“…Several studies indicate that autophagy plays a key role in controlling muscle mass by protein degradation (Mommsen 2004;Salem et al 2006;Seiliez et al 2012). Most components of autophagy and its associated signaling pathways (AKT1, TOR, AMPK, FOXO) are evolutionarily conserved in the rainbow trout (Polakof et al 2011;Seiliez et al 2008;Seiliez et al 2012). Using qRT-PCR and Western blot analysis, Seiliez and colleagues were able to demonstrate that fasting fish or serum depletion of trout myocytes strongly induces the expression of several major genes involved in autophagy (LC3B, gabarapl1, atg12l, atg4b), suggesting that autophagy is acting as a cell survival mechanism to provide the energy and the nutrients essential for allowing fish to survive during nutritional starvation (Seiliez et al 2010).…”
Section: Autophagy Induced By Environmental Stress On Aquatic Invertementioning
confidence: 99%
“…Primary antibodies for the analysis of the insulin signaling pathway were obtained from Cell Signaling Technologies (Akt-p #9272; Akt #9271; mTOR-p #2972; mTOR#2971S; S6-p #4856S; S6 #2217S). All were used at a dilution of 1:1000 and have previously been shown to cross-react with rainbow trout proteins of interest (Seiliez et al 2008). After incubation with a goat anti-rabbit IRDye infrared secondary antibody (LI-COR Inc. Biotechnology), bands were visualized and quantified by Infrared fluorescence using the OdysseyH Imaging System (LI-COR Inc.…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%